SUPERVISI PEMBINAAN MORAL MELALUI HALAQAH QUR’AN(STUDI KASUS DI SD INTEGRAL LUKMANUL HAKIM KEC. KUMAI KOBAR KALTENG) - Ummu Hany; Musyarapah Musyarapah (CV. ADIBA ASIHA AMIRA, 2022)
This research is motivated by the utilization of the results of supervision by school principals for coaching. The formulation of the problem in this research is how the implementation of moral supervision is carried out, what approach is used in moral supervision. The success and destruction of a civilization can be seen from the character, personality, responsibilities and progress of the children and the younger generation. A great and noble civilization will give birth to children and young people who are strong and reliable. On the other hand, a corrupt and despicable civilization will only make children and young people weak, corrupt and even destructive. The first system carried out by the Prophet in the coaching or cadre process was through the halaqah method. The Messenger of Allah sat in a place, then the friends listened to advice, learning, motivation, etc. By forming a circle. This system has been running since the Prophet's first preaching at the house of Arqam bin Abil Arqam. For this reason, the supervision process is needed in moral development by the teacher which will then be transferred to the child. The importance of moral development in this case will foster a reciprocal relationship which will eventually give rise to mutual trust, openness and flexibility. The impact of moral development in schools makes a commitment to practice teaching that can be imitated by students, has social value and fosters social awareness. Supervision of moral development is carried out through the halaqah approach which is carried out in an effort to improve the quality of educational resources, especially related to morality itself. Teachers are a component of human resources that must be nurtured and developed continuously. If observed, not all teachers who are educated in educational institutions are properly trained. Potential resources must be continuously grown and developed. In essence, supervision is in addition to coaching towards improving the situation. In the context of schools in educational organizations, supervision is a very important part of the school management and administration process. Through supervision, it is a strategic step in maximizing all programs and responsibilities, because supervision is one of the strategies that determine success in improving an organization. Whether you realize it or not, sometimes in the supervision process carried out by a supervisor, there is a moral element in it. Which as a basis where the moral dimension should be more clearly visible or firmly applied. This research is included in qualitative research. This is done by collecting, sorting, grouping print and electronic references related to the basics of fostering moral supervision through the halaqah of the Qur'an. The findings and conclusions of this study are through the halaqah of the Qur'an as a strategic step in implementing moral-related educational supervision. Supervision as a moral action is not a limitation of human freedom, but the norm seeks to protect, cultivate values, and help humans to gain prosperity in their lives. In the supervision of moral improvement strategies it is better if we understand the moral dimension of supervision by looking more closely at the dimensions included in ideal teaching. The results of this study indicate that the existence of moral development in the halaqah of the Koran is very effective in instilling moral values in students through exemplary stories found in the Koran, sirah nabawiyah material, stories of the scholars and others. After participating in the Al-Qur'an halaqah coaching activities, students are more focused, affected by the bond between murobbi and students because this coaching system is very qualified as implemented by the Prophet. Provide positive benefits for students, especially in adding religious insight and spirit of togetherness.